2014
DOI: 10.1016/j.cell.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Autophagic Membrane-Scaffold Assembly and Disassembly

Abstract: Autophagy is a catabolic pathway that sequesters undesired cellular material into autophagosomes for delivery to lysosomes for degradation. A key step in the pathway is the covalent conjugation of the ubiquitin-related protein Atg8 to phosphatidylethanolamine (Atg8-PE) in autophagic membranes by a complex consisting of Atg16 and the Atg12-Atg5 conjugate. Atg8 controls the expansion of autophagic precursor membranes, but the underlying mechanism remains unclear. Here, we reconstitute Atg8 conjugation on giant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
227
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(235 citation statements)
references
References 42 publications
8
227
0
Order By: Relevance
“…Indeed, as the yeast ATG5 complex has membrane tethering capabilities 11 , it is tempting to speculate that such complex could also be involved in tethering the phagophore membrane to the underlying ER membrane, and in controlling sealing of the phagophore aperture. The idea of an additional role for ATG5 complexes, beside catalysis of ATG8 lipidation, is consistent with recent work showing that ATG12-ATG5-ATG16 complexes and lipidated ATG8 can assemble in a functionally relevant 2D meshwork on membranes 42 . It is therefore possible that regulated formation and disassembly of such meshwork at the ATG5-labelled domain of the phagophore underlie the control of its expansion and closure, in interaction with the cargo.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, as the yeast ATG5 complex has membrane tethering capabilities 11 , it is tempting to speculate that such complex could also be involved in tethering the phagophore membrane to the underlying ER membrane, and in controlling sealing of the phagophore aperture. The idea of an additional role for ATG5 complexes, beside catalysis of ATG8 lipidation, is consistent with recent work showing that ATG12-ATG5-ATG16 complexes and lipidated ATG8 can assemble in a functionally relevant 2D meshwork on membranes 42 . It is therefore possible that regulated formation and disassembly of such meshwork at the ATG5-labelled domain of the phagophore underlie the control of its expansion and closure, in interaction with the cargo.…”
Section: Discussionsupporting
confidence: 73%
“…The proteolytic activity of this protein is also crucial during the final steps of autophagosome formation when Atg4 cleaves Atg8 again to release it from its lipid anchor (Kirisako et al, 2000). Although it has been proposed that Atg4 processes lipidated Atg8 on all membranes except autophagosomal ones (Nakatogawa et al, 2012), recent in vitro data have shown that Atg4 activity is crucial for the disassembly of an eventual autophagosome protein coat formed by Atg8 and the Atg12-Atg5-Atg16 complex (Kaufmann et al, 2014). This scenario requires that Atg4 activity is tightly regulated to ensure that vesicle uncoating occurs precisely upon autophagosome completion.…”
Section: Disassembly Of the Atg Machinerymentioning
confidence: 99%
“…Such a mechanism might be at work in the early fusion of incoming vesicles, as suggested for Atg9-containing vesicles (Mari et al, 2010;Yamamoto et al, 2012). Another study, also using yeast proteins, showed that once lipidated Atg8 is formed, it can anchor the Atg12-Atg5-Atg16 complex to the membrane through a specific Atg8-Atg12 interaction, leading to the assembly of a 'coat-like' scaffold at the convex side of the phagophore (Kaufmann et al, 2014). At the concave side, binding of cargo or cargo adaptors through Atg8-LIR-sequence interactions would outcompete the binding of Atg8 to Atg12, providing an explanation as to why Atg16-Atg12-Atg5 is exclusively found on the outer phagophore membrane (Mizushima et al, 2011).…”
Section: Membrane Curvature Of Autophagosomesmentioning
confidence: 99%